Implementation of Universal Design in Inclusive Architectural Planning to Improve Accessibility of Urban Public Spaces: Systematic Literature Review - Bara Junizar Dean Raffarin; Heru Prasetyo Utomo (Faculty of Engineering, Universitas Islam Darul Ulum Lamongan, 2026)
Urban public space planning plays a strategic role in ensuring the fulfillment of access rights for diverse communities in physical, social, and cognitive terms. Universal design emerges as a design approach aimed at creating built environments that can be used equitably by all users without the need for special adaptation. Although this principle has been normatively recognized in various international and national legal instruments, its implementation in the practice of urban public space architectural planning still shows significant gaps. This study aims to analyze the application of universal design principles in inclusive urban public space architectural planning and to identify the level of their integration within spatial layout, circulation, facilities, and user experience elements. The study employs a systematic literature review (slr) approach following prisma guidelines, examining peer-reviewed journal articles published between 2021 and 2025 and retrieved from four major databases. Out of a total of 750 identified articles, 30 met the inclusion criteria and were analyzed thematically. The findings indicate that research on universal design has increased significantly over the past five years, with a predominance of qualitative approaches and a focus on public open spaces. The integration of universal design in planning practice remains partial, tends to be oriented toward compliance with technical standards, and has not yet fully centered on user experience and independence.